2019
DOI: 10.3390/su11154169
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Management of Nutria (Myocastor coypus) Populations in South Korea

Abstract: In 2014, the South Korean government initiated the “Nutria Eradication Project” to actively manage and control populations of nutria, an invasive alien species that threatens national biodiversity. In the present study, we examined domestic nutria habitats in 2014 to 2018 and analyzed spatial shifts in habitat distribution to develop management policies and eradication strategies for the South Korean Ministry of Environment. A total of 27,487 nutria individuals were captured over five years upon the initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 24 publications
2
43
1
Order By: Relevance
“…In line with previous nutria distribution studies in South Korea, the kernel density results support the middle and lower reaches of the Nakdong River having slow water flow leading to tributaries and wetlands, with a warm winter and abundant food sources, providing a good habitat for nutria populations to establish and proliferate [19,50]. A previous investigation reported that nutria management efforts are focused on the Nakdong River basin in South Korea because nutria individuals are mainly clustered in this region [22]. Although the previous management was effective to decrease nutria habitat tracks, we tried to apply genetic analysis for the developed nutria eradication project in South Korea.…”
Section: Nutria Distribution and Tissue Samplingsupporting
confidence: 87%
See 4 more Smart Citations
“…In line with previous nutria distribution studies in South Korea, the kernel density results support the middle and lower reaches of the Nakdong River having slow water flow leading to tributaries and wetlands, with a warm winter and abundant food sources, providing a good habitat for nutria populations to establish and proliferate [19,50]. A previous investigation reported that nutria management efforts are focused on the Nakdong River basin in South Korea because nutria individuals are mainly clustered in this region [22]. Although the previous management was effective to decrease nutria habitat tracks, we tried to apply genetic analysis for the developed nutria eradication project in South Korea.…”
Section: Nutria Distribution and Tissue Samplingsupporting
confidence: 87%
“…The Korean Ministry of Environment began investigating the status of nutrias in 2006 and designated the nutria as an invasive alien species in 2009. Previous studies reported that the settlement of nutrias in South Korea is concentrated in the Nakdong River basin [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations